PP‐GF‐EPP sandwich structures as housing materials for rechargeable energy storage system of electric vehicles: Investigations into flame retardancy. (7th February 2022) - Höhne, Carl‐Christoph; Gettwert, Volker; Kilian, Sascha; Tillner, Benjamin; Jahn, Ivonne; Menrath, Andreas
Abstract: The growing importance of electric mobility has led to an increased demand for safety technologies in the automotive sector, such as the flame retardancy of materials used for electric vehicles. The fire protection of a fully equipped rechargeable energy storage system (REESS), including battery, housing, control electronics, etc., against a fuel fire must be tested according to UNECE Regulation No. 100 Annex 8E ‐ Fire Resistance (UNECE‐R100‐8E). To pass this fire retardancy requirement, the flame retardancy of the housing materials is of great importance. In this study, the flame retardancy of glass‐fiber‐reinforced polypropylene (PP‐GF) tape laminates containing the flame retardant magnesium hydroxide and different GF amounts, as well as sandwich structures of these PP‐GF tape laminates with a polypropylene bead foam (EPP) core, are investigated by a limiting oxygen index test, a UL94 test and a cone calorimeter test. Furthermore, a newly developed approach of a bench‐scale fuel fire test which simulates the fire treatment of the UNECE‐R100‐8E on component level is used. Abstract : In this study, the flame retardancy of glass‐fiber‐reinforced polypropylene (PP‐GF) tape laminates containing the flame retardant magnesium hydroxide (MDH) and different GF amounts, as well as sandwich structures of these PP‐GF tape laminates with a polypropylene bead foam (EPP) core, are investigated by a limiting oxygen index (LOI) test, a UL94 test, a cone calorimeter test and a newly developed approach of a bench‐scale fuel fire test which simulates the fire treatment of the UNECE‐R100‐8E on component level.